PERANCANGAN SISTEM PEREKRUTAN SECURITY BADAN USAHA JASA PENGAMANAN BERBASIS WEB PADA PT. KRAKATAU JASA INDUSTRI - Sawitri Nurhayati; Teuku Fadjar Shadek; Darpi Darpi; Dodi Lasandi (LPPM Unbaja, 2025)
The recruitment of security personnel at PT Krakatau Jasa Industri is an organized process involving prospective security employees who work directly in the field of security. Currently, the management of security candidate data at PT Krakatau Jasa Industri is still done manually, using job application documents, followed by entering the security employee data into Microsoft Excel. Additionally, there is a lack of supervision over prospective security employees. The objective is to facilitate the recruitment process at PT Krakatau Jasa Industri quickly and accurately, while also enabling better monitoring of new security candidates. Data collection methods include observation, interviews, and literature studies. The research method used is the waterfall model. The system design tools used include UML (Unified Modeling Language), specifically the Use Case Diagram, Class Diagram, Activity Diagram, and Sequence Diagram. The system is implemented using PHP (Hypertext Preprocessor) programming language and MySQL as the Database Management System. The result of this research is a web-based system designed to manage the recruitment data of security personnel at PT Krakatau Jasa Industri, simplifying the recruitment process.